Analysis of Production Priority using Winter Forecasting Method and Analytical Hierarchy Process - Ary Fitriyono; Raditya Indra Kusuma; Humiras Hardi Purba (JURNAL TEKNIK INDUSTRI, 2019)
Forecasting is a tool to determine the extent of future conditions which will affect decisions on the strategic policy direction. Making the best decisions requires an analysis tool as a means for the level of accuracy can be achieved. This paper aims to forecast sales conditions radiator type A, type B and type C in 2016 and set priorities based on the results of analysis AHP production. The method used in forecasting using the method of Winter and decision analysis using AHP Pairwise comparison. Forecasts for radiator type A and type B tend to fluctuate while the linear C-type radiator, resulting in the production of type C are preferred. AHP analysis results indicate that the radiator of type C have a dominant score on the criteria of Production (0.382), Selling Price (0.376), Design (0.340), and Market Segment (0.329). As for Durability criteria, type B has the highest score of 0.391. Changes in sensitivity criteria has no significant effect on C-type radiator, so that it can be concluded radiator type C is a priority in radiator production line at company X for 2016.